Controlling the self-assembly and optical properties of gold nanoclusters and gold nanoparticles biomineralized with bovine serum albumin. Issue 122 (24th November 2015) - McDonagh, Birgitte H.; Singh, Gurvinder; Bandyopadhyay, Sulalit; Lystvet, Sina M.; Ryan, Joseph A.; Volden, Sondre; Kim, Eugene; Sandvig, Ioanna; Sandvig, Axel; Glomm, Wilhelm R.
Abstract : While the size-dependent optical properties of BSA-stabilized gold nanoclusters are well known, the time-dependent growth mechanism remains to be described. Abstract : While the size-dependent optical properties of BSA-stabilized gold nanoclusters are well known, the time-dependent growth mechanism remains to be described. Herein, we systematically compare two synthesis methods with and without ascorbic acid, and show that tuning of BSA-stabilized gold nanoclusters (AuNCs) of different sizes can be performed without the aid of an extrinsic reducing agent and with good reproducibility. We also show that adding ascorbic acid yields larger BSA-stabilized gold nanoparticles (AuNPs), and that AuNPs can only form above a threshold gold precursor concentration. Using computed tomography, we describe how these biomineralized AuNPs show size-dependent X-ray attenuation. Growth of BSA-stabilized AuNCs and AuNPs, over a range of gold precursor concentrations, was followed with steady-state fluorescence and UV-vis spectroscopy for one week, constituting the first study of its kind. Based on our results, we propose a mechanism for BSA-stabilization of AuNCs and AuNPs that can further aid in selective growth of discrete AuNCs and AuNPs.